Efek Pemediasian Kepercayaan terhadap Pengaruh Kepemimpinan Transformasional pada Komitmen Pegawai Satpol-PP di Eks Karesidenan Banyumas - Indrayanto, Adi (Jurnal Aplikasi Manajemen, 2012)
The research aims to investigate and examine the mediating effect of on employees'trust, in thecontext of transformational leadership at Civilian Para-Police Force Institution in Banyumas Area. It isexpected that the result of the research will provide an account to human resources management literaturewith regards to transformational leadership issue.The research is an explanatory study which attempts toexamine and describe the variables using cross-sectional data analysis. Quantitative approach and indepthinterview are employed in this research. The research population consists of all employees of CivilianPara-Police Force Institution in Banyumas Area (Banyumas, Purbalingga, Cilacap, dan Banjarnegararegency). Total number of the population is 266 employees, but only 132 respondents returned the questionnaires;thus, the response rate is 74%. Proportional random sampling is employed as the samplingtechnique of the research. Structural Equation Modeling (using AMOS software) is performed for dataanalysis purpose. The result shows that trust has mediating effect on the relationship between transformationalleadership and employees'commitment. The result provides an account in establishing a model oftransformational leadership that will be more effective and suitable for this kind of organization (CivilianPara-Police Force Institution).